2005
DOI: 10.2151/jmsj.83.727
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Madden-Julian Oscillation by ENSO: Inferences from Observations and GCM Simulations

Abstract: The impact of the El Niñ o-Southern Oscillation (ENSO) on the Madden-Julian Oscillation (MJO) is studied, based on reanalysis data and output from an ensemble general circulation model (GCM) experiment. Observed monthly sea surface temperature variations over the period of 1950-99 are imposed in the deep tropical eastern/central Pacific in the course of the SST experiment. Both GCM, and reanalysis data, indicate that intraseasonal activity of the low-level zonal wind is enhanced (reduced) over the central (wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 40 publications
6
39
0
Order By: Relevance
“…By contrast, during CP El Niño winters (Fig. 5), the MJO emerges over the western Indian Ocean, and can maintain or even enhance its intensity over the region west of 120 • E, which is in agreement with previous studies (Kessler, 2001;Tam and Lau, 2005). However, the propagation tends to be concentrated to the west of the dateline, and convection anomalies become greatly reduced to the east of 180 • .…”
Section: Extent Of Mjo Eastward Propagationsupporting
confidence: 90%
See 1 more Smart Citation
“…By contrast, during CP El Niño winters (Fig. 5), the MJO emerges over the western Indian Ocean, and can maintain or even enhance its intensity over the region west of 120 • E, which is in agreement with previous studies (Kessler, 2001;Tam and Lau, 2005). However, the propagation tends to be concentrated to the west of the dateline, and convection anomalies become greatly reduced to the east of 180 • .…”
Section: Extent Of Mjo Eastward Propagationsupporting
confidence: 90%
“…These previous studies indicate a two-way interaction between enhanced MJO activity and the development of El Niño (Kessler and Kleeman, 2000;Marshall et al, 2016). Besides, the MJO extends further east to the central Pacific during El Niño events, which is associated with the warmer SST beneath (Kessler, 2001;Tam and Lau, 2005). Further study suggests that the lifetime of the MJO is also dependent on the state of ENSO: the MJO propagates faster through the Maritime Continent and western Pacific during El Niño (Pohl and Matthews, 2007).…”
Section: Introductionmentioning
confidence: 75%
“…Both ENSO and MJO are involved in the shifts of the large-scale convection and atmospheric circulation in the tropics. The connection between the two modes, however, is complicated and ambiguous (Hendon et al, 1999(Hendon et al, , 2007Slingo et al, 1999;Tam and Lau, 2005). Slingo et al (1999) and Hendon et al (1999) reported that there is no obvious correlation between the year-to-year MJO amplitude and ENSO.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, pronounced MJO events produce westerly wind passage in the western Pacific, a key factor for the onset and development of ENSO (Harrison and Schopf, 1984;Kessler et al, 1995;Belamari et al, 2003;Wang et al, 2013). On the other hand, ENSO may impact the evolution of the MJO in space and time through changing the background convection in the tropical Pacific (Hendon et al, 1998;Takayabu et al, 1999;Tam and Lau, 2005;Pohl and Matthews, 2007;Roundy and Kravitz, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Tam and Lau (2005) found that the phase speed of wintertime ISO (MJO) is modulated by the ENSO. Yun et al (2009) discussed the influence of East Asian summer ISO on the ENSO in a quasi-biennial time scale.…”
Section: Introductionmentioning
confidence: 99%